Destiny and destination the extraordinary story and history of Holy Angel University 1933-2008 - Tantingco, Robert P. (Holy Angel University, 2009)
"This year [2008], Holy Angel University is celebrating its 75th. Its founders would probably not be surprised that the schools they put up in 1933 has lived this long. What they never could have imagined is how big it has become and how faithful it has remained to their original mission"--Book jacket.